Personal care compositions containing complexed polyelectrolytes
By using a specific proportion of cationic polyelectrolytes and anionic polyelectrolytes in the cleaning composition, the problems of low deposition rates and potential irritation in the prior art are solved, and better deposition effects of conditioning agents and beneficial agents and skin sensation enhancement are achieved.
Patent Information
- Application Number
- CN202411291647.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2016-09-28
- Filing Date
- 2017-06-21
- Publication Date
- 2024-12-13
AI Technical Summary
Existing cleaning compositions have problems with low deposition rates, potential irritation of surfactants and insufficient assistance to water-soluble components during cleaning, especially when complexing of cationic polymers and anionic surfactants, It is difficult to effectively deposit conditioning agents and beneficial agents.
Using a composition containing cationic polyelectrolyte and anionic polyelectrolyte, the dry precipitate mass yield at dilution is improved by optimizing its weight ratio (about 0.05 to 1.2), thereby improving the deposition effect of conditioning agents and beneficial agents and reducing surfaces. The amount of active agent deposited.
The deposition effect of conditioning agents and beneficial agents is significantly improved, the skin feeling after application is improved, and the amount of surfactant is used is reduced, and the performance of the cleaning composition is improved.
Smart Images

Figure BDA0005044781850000121 
Figure BDA0005044781850000131 
Figure BDA0005044781850000141
Abstract
Description
[0001] This application claims the benefit of U.S. Provisional Application No. 62 / 352,713, filed June 21, 2016, the entire disclosure of which is hereby incorporated by reference herein for all purposes. Technical Field
[0002] The present invention relates to personal care compositions containing complex polyelectrolyte benefit ingredients. Background Art
[0003] Surfactant-based compositions are commonly used to clean keratinous surfaces (e.g., skin and hair) to remove dirt, stains, and excess sebum. However, the disadvantage of this cleaning method is that during cleaning, it removes important / advantageous components of the keratinous surface. This can lead to unpleasant sensations, for example, hair may be astringent, tangled, and difficult to arrange, and may lose softness and luster, and / or the skin or scalp may feel dry, tight, and / or itchy, and in some cases red. In addition, in addition to foaming and removing dirt, stains, and excess sebum, it is desirable to provide a beneficial effect from a cleaning composition. A variety of approaches have been developed to mitigate the shortcomings in the cleaning process, and to enhance additional beneficial effects in addition to foaming and cleaning. For example, a cleaning composition may include (in addition to a surfactant) oils (such as silicone oils, vegetable oils, and mineral oils) to provide, for example, a soft feel and enhance the moisture retention of the cleaned surface. It is also quite common to incorporate cationic components (in most cases cationic polymers) into cleaning compositions to provide enhanced sensory attributes (e.g., softness) or improved functional qualities (e.g., anti-tangling and anti-static benefits) to the cleaned surface. These types of additives in cleaning compositions are often referred to as conditioners. Cleaning compositions may also contain additional benefit agents, such as zinc pyrithione, salicylic acid, or hyaluronic acid. In order for these conditioners and benefit agents to be effective, they must be deposited onto the surface (e.g., skin and hair) during the cleaning process.
[0004] A common challenge encountered in cleaning compositions is the effectiveness of the deposition of conditioning and benefit agents on the cleaned surface. Typically, only a portion of the agents are deposited, while the rest are washed / rinsed away. The keratin surface characteristically carries some anionic surface charge; therefore, cationic components can attach to the keratin surface to a certain extent through electrostatic interactions. Therefore, cationic components (especially cationic polymers) are used as conditioning agents in cleaning compositions. Cationic polymers can enhance the deposition of conditioning agents (e.g., emollients, oils, other benefit agents) and the cationic polymers themselves through a process generally referred to as "coagulation" or "complexation" or "dilution precipitation". In this process, during use of the cleaning composition (i.e., upon dilution), the cationic polymers form insoluble complexes with anionic surfactants. These insoluble complexes or coacervates can enhance the deposition of cationic polymers and water-insoluble components (such as oils).
[0005] The concept of combining anionic surfactants and cationic polymers is used today in many cleaning compositions. The formation of coacervates depends on various criteria such as molecular weight, charge density, pH and temperature. Coacervate systems and the effects of these parameters have been studied previously and are disclosed, for example, in J. Caelles et al., Cosmetics & Toiletries, Vol. 106, April 1991, pp. 49-54; CJ van Oss, J. Dispersion Science and Technology, Vol. 9 (5, 6), 1988-1989, pp. 561-573; DJ Burgess, J. of Colloid and Interface Science, Vol. 140, No. 1, November 1990, pp. 227-238; S. Zhou et al., Langmuir, 20, 2004, 8482-8489 and C. Lepilleur et al., J. Cosmet. Sci., 62, March / April 2011, 161-177. Therefore, methods for improving the deposition of cleaning compositions include optimizing the cationic polymer and optimizing the surfactant system. Optimization of cationic polymers includes changing the cationic charge density, molecular weight, backbone chemistry, and chemistry of the cationic moiety. Typically, the surfactant system in the cleaning composition is adjusted to the specific cationic polymer used to improve efficiency, compatibility, and formulation stability (or vice versa). Several examples of these approaches are disclosed in U.S. Patent Application No. 2003 / 0108507 and references therein.
[0006] However, this reference also discloses that the deposition effect of small dispersed actives (i.e., benefit agent materials that are insoluble in the cleansing formulation and suspended in the cleansing formulation as particles or droplets) with a size less than or equal to 2 μm is only 2%-3% (200-300 ppm / % active level in the formulation). The deposition effect of only 2%-3% indicates a general need to improve the deposition effect of cleanser formulations. In addition, the use of anionic surfactants and cationic polymer complexes will result in the deposition of a certain amount of anionic surfactant (present in the coacervate) on the keratinous surface. The deposition of anionic surfactants is undesirable because they can exhibit potential high irritation when left on the skin surface, and anionic surfactants can damage the keratinous components of the skin and hair, which can cause undesirable morphological changes to these substrates.
[0007] Additionally, compositions utilizing complexes of anionic surfactants and cationic polymers generally do not provide any enhancement / assistance in depositing water soluble benefit agents since such benefit agents are not effectively entrapped in the polymeric surfactant coacervate upon dilution and thus do not deposit.
[0008] Another method to enhance the deposition effect of certain benefit agents described in the prior art is to introduce cationic charges into the benefit agents, such as emollients, moisturizers and waxes. Cationic charges can promote the attachment of benefit agents to surfaces with anionic surface charges, such as hair and skin. However, such methods require chemical modification of the benefit agents with additional cationic moieties, or encapsulation of the benefit agents with cationic materials, both of which may or may not be feasible.
[0009] It is reported that in the prior art, the presence of anionic polymers in compositions containing cationic polymers and anionic surfactants does not lead to any improvement in the deposition effect. For example, it has been demonstrated that anionic rheology modifier polymers (such as carbomers and acrylate copolymers) have an adverse effect on the deposition effect, such as disclosed in WO 2014 / 137859 A1. Specifically, the reference states that the presence of typical rheology polymers (e.g., anionic acrylic copolymers (such as Carbopols) does not improve the deposition effect of silicone oil. In addition, when the particle size of the silicone oil is small (e.g., the average oil droplet size is less than 5 microns), it even seriously reduces the deposition effect of the silicone oil. The reference also states that "silicone deposition is inversely proportional to the amount of acrylic stabilizer thickener present." The reference discloses the use of non-ionic amphiphilic rheology modifier polymers to stabilize the composition "without interfering with the deposition of the silicone material" and does not mention how to improve the deposition effect.
[0010] In summary, despite the various methods used in the prior art to improve the conditioning and deposition of cleaning formulations, the prior art still suffers from deficiencies such as low deposition rates, potential irritation of deposited surfactants, limited compatibility with anionic polymers, and lack of assistance in depositing water-soluble components compared to surfactants. Therefore, it remains desirable to provide improved cleaning compositions with optimal performance and enhanced deposition. Summary of the invention
[0011] The present invention provides compositions comprising: a) a cationic polyelectrolyte, b) at least one surfactant; and c) from about 0.01% to about 1.2% by weight of an anionic polyelectrolyte in a cosmetically acceptable aqueous medium. The weight ratio of the anionic polyelectrolyte to the cationic polyelectrolyte is from about 0.05 to about 1.2. The compositions of the present invention exhibit a viscosity change below a minimum significant change threshold (Δη) when compared to a substantially identical composition, but without the presence of from about 0.01% to about 1.2% by weight of the anionic polyelectrolyte and having a weight ratio of the anionic polyelectrolyte to the cationic polyelectrolyte of from about 0.05 to about 1.2. min ) and showed no measurable increase in yield stress or yield stress value. DETAILED DESCRIPTION
[0012] The cleaning composition of the present invention comprises a combination of a cationic polyelectrolyte and an anionic polyelectrolyte. The amount of the anionic polyelectrolyte is selected so that the anionic polyelectrolyte is sufficient to increase the amount of dry precipitate mass yield when diluted and maintain effective cleaning efficacy without having the adverse effect of changing the rheological properties of the composition. If the weight ratio of the anionic polyelectrolyte to the cationic polyelectrolyte is from about 0.05 to about 1.2, the anionic polyelectrolyte does not increase the dry precipitate mass yield.
[0013] The specific combination of one or more anionic polyelectrolytes and one or more cationic polyelectrolytes in the surfactant system described herein is referred to as a "polyelectrolyte regulating system". As used herein, "polyelectrolyte regulating system" refers to a combination of one or more anionic polyelectrolytes and one or more cationic polyelectrolytes, wherein the one or more anionic polyelectrolytes and the one or more cationic polyelectrolytes are present in a weight ratio of about 0.05 to about 1.2 for the weight ratio of the anionic electrolyte to the cationic polyelectrolyte, and the concentration of the anionic polyelectrolyte is from about 0.01 wt % to about 1.2 wt % based on the total weight of the cleaning composition.
[0014] The compositions of the present invention comprising such polyelectrolyte regulating systems exhibit improved deposition efficacy of conditioning agents and benefit agents compared to similar compositions not comprising such polyelectrolyte regulating systems, and provide additional benefits, such as improved skin feel after application or reduced amount of deposited surfactants. Preferred weight ratios of anionic polyelectrolytes to cationic polyelectrolytes include from about 0.05 to about 1.2, or from about 0.1 to about 1.2, or from about 0.1 to about 1. As measured as described below, when anionic polyelectrolytes within a specific range are present, the mass yield of dry precipitates upon dilution is increased by 10% or more compared to compositions that are substantially the same but do not contain such an amount of anionic polyelectrolytes. More preferably, the mass yield of dry precipitates upon dilution increases by 20% or more, or even more preferably by 40% or more.
[0015] As mentioned above, the weight ratio of anionic polyelectrolyte to cationic polyelectrolyte is crucial. Typically, at a ratio of about 0.05 to about 1.2, the composition exhibits an increased dry precipitate mass yield when diluted. According to the type of polyelectrolyte, surfactant system and other formulation parameters (e.g., salt concentration), to achieve the maximum dry precipitate mass yield, the optimal weight ratio of anionic polyelectrolyte to cationic polyelectrolyte can vary within this range. The increase in dry precipitate mass yield during the dilution of the cleaning composition is an indication of improved deposition effects of conditioning agents and benefit agents. In addition, the increase in dry precipitate mass yield indicates that anionic polyelectrolyte is part of the coacervate formed during dilution, and therefore also deposits. However, compared with cationic polyelectrolytes, incorporating too many anionic polyelectrolytes into the composition (i.e., when the ratio of anionic polyelectrolyte mass to cationic polyelectrolyte mass is greater than about 1.2) will result in no improvement, or even performance degradation when compared with compositions without anionic polyelectrolytes.
[0016] Where applicable, chemicals are designated by their INCI names. Additional information, including suppliers and trade names, can be found in the International Cosmetic Ingredient Dictionary and Handbook, 15 th The information can be found in the appropriate INCI monograph in the 2011 Edition and is also available through the PCPC online information library (http: / / online.personalcarecouncil.org / jsp / Home.jsp).
[0017] Unless otherwise expressly stated, all percentages listed in this specification are percentages by weight. The percentages and weights of components such as polyelectrolytes, surfactants, salts, polymers, acids, etc. listed in this specification are the percentages and weights of the active substances of the components, excluding, for example, solvents (such as water added to the sodium chloride aqueous solution in the composition).
[0018] As used herein, "substantially the same composition" refers to a composition that is substantially the same as the composition of the present invention, but with a difference in the relative amounts of anionic polyelectrolyte and cationic polyelectrolyte.
[0019] As used herein, "wt %" means percent by weight, ie, weight / weight %; for example, 5 grams of sodium chloride in 95 grams of water is a 5 wt % active sodium chloride solution in water.
[0020] Anionic polyelectrolyte
[0021] Anionic polyelectrolytes are polymers with multiple anionic charges, i.e., the polyelectrolyte comprises monomers or repeating units with anionic moieties. Suitable moieties with anionic charges may be, but are not limited to, CO2 - 、SO3 - 、SO4 - PO3 2- and PO4 2- The compositions of the present invention comprise from about 0.01 wt. % to about 1.2 wt. % of anionic polyelectrolyte.
[0022] The charge density of the anionic polyelectrolyte is about 0.1 milliequivalents / gram (meq / g) or greater, more preferably about 0.1 to 10 meq / g, more preferably about 0.5 to 5 meq / g, even more preferably about 0.5 to 4 meq / g, and the weight average molecular weight (Mw) is about 10,000 g / mol or greater, more preferably about 50,000 g / mol or greater. The molecular weight of the non-crosslinked anionic polyelectrolyte is about 50,000 to 3,000,000 g / mol, more preferably about 50,000 g / mol to 1,000,000 g / mol. The crosslinked polyelectrolyte is usually defined by its primary particle size rather than molecular weight. The preferred primary particle size of the crosslinked anionic polyelectrolyte is about 0.01 micron (μm) or greater, more preferably about 0.1 μm or greater, 1000 μm or less, more preferably about 100 μm or less. Examples of cross-linked anionic polyelectrolytes are, for example, acrylate copolymers, such as Aqua SF-1, having a primary particle size of about 0.2 μm; and polyacrylate superabsorbent polymer particles, having a particle size of about 25-500 μm.
[0023] Suitable anionic polyelectrolytes include, but are not limited to: 1) polyelectrolytes derived from ethylenically unsaturated monomers comprising anionic monomers or anionizable monomers; 2) anionic and anionizable polysaccharides and polysaccharide derivatives; and 3) other anionic polyelectrolytes containing natural polymer chains (e.g., polysaccharides or protein chains) as well as synthetic polymers (e.g., polyethylene glycol or acrylate (co)polymers), such as anionic / anionizable polypeptides / proteins, anionic / anionizable hybrid (co)polymers.
[0024] Non-limiting examples of such polyelectrolytes are described in the International Cosmetic Ingredient Dictionary and Handbook, 15, published by the Personal Care Products Council (PCPC), Washington DC. th The FDA has issued a directive to the Administration of Infectious Diseases (ADAS) for use with this product, which is described in the corresponding INCI monograph in FDA Edition.
[0025] Polyelectrolytes derived from ethylenically unsaturated monomers including anionic monomers / anionizable monomers include, but are not limited to (a) linear non-crosslinked (co)polymers, including non-crosslinked alkali-swellable emulsion (ASE) polymers; (b) crosslinked (co)polymers, including crosslinked ASE polymers (xASE); and (c) hydrophobically modified derivatives of the (co)polymers described in (a) and (b), including non-crosslinked and crosslinked hydrophobically modified alkali-swellable emulsion (HASE and xHASE) polymers.
[0026] Examples of anionic / anionizable ethylenically unsaturated monomers include acrylic acid, methacrylic acid, vinyl sulfonic acid, vinyl sulfuric acid, vinyl phosphonic acid, vinyl phosphoric acid, vinyl boric acid, citraconic acid, maleic acid, fumaric acid, crotonic acid, itaconic acid, methacryloxyethyl phosphate, methacryloxyethyl sulfuric acid, methacryloxyethyl sulfonic acid and 2-acrylamidomethylpropanesulfonic acid (AMPSA), 2-methyl-2-acrylic acid ethyl-2-phosphate (HEMA-phosphate), methacryloxy PPG-7 phosphate, β-carboxyethyl acrylate, 3-acrylamido-3-methylbutyric acid (AMBA), and mixtures thereof.
[0027] As used herein, the term "(co)polymer" is meant to include polyelectrolytes derived substantially from one type of monomer (homopolymers), as well as polyelectrolytes derived from more than one type of monomer (copolymers).
[0028] The anionic polyelectrolytes derived from ethylenically unsaturated monomers of the present invention can be synthesized via free radical polymerization techniques known in the art. On the other hand, bulk polymerization, solution polymerization, precipitation polymerization or emulsion polymerization techniques can be used to synthesize the anionic polyelectrolytes derived from ethylenically unsaturated monomers of the present invention.
[0029] As used herein, the term "linear non-crosslinked (co)polymer" of the present invention refers to an anionic polyelectrolyte made from ethylenically unsaturated monomers, which contain one or more anionic / anionizable ethylenically unsaturated monomers and optionally one or more nonionic or amphoteric ethylenically unsaturated monomers. Examples of nonionic or amphoteric ethylenically unsaturated monomers include, but are not limited to, ethyl (meth)acrylate, butyl (meth)acrylate, vinyl formate, vinyl acetate, 1-methylvinyl acetate, vinyl propionate, vinyl butyrate, (meth)acrylamide, dimethylacrylamide, sulfobetaine acrylate (e.g., 3-methacrylamidopropyl dimethylquaternary ammonium propanesulfonate) and mixtures thereof. Examples of anionic linear non-crosslinked (co)polymers include, but are by no means limited to, poly (meth)acrylic acid homopolymers or acrylamide-(meth)acrylic acid copolymers. As used herein, the term "(meth)acrylic" acid refers to corresponding methyl derivatives including acrylic acid, and "(meth)acrylate" refers to methyl derivatives including alkyl acrylates and salt forms of acrylic acid. For example, "(meth)acrylic" acid refers to acrylic acid and / or methacrylic acid, "(meth)acrylate" refers to alkyl acrylate and / or alkyl methacrylate, and "sodium (meth)acrylate" refers to sodium acrylate and / or sodium methacrylate. The linear non-crosslinked (co)polymers are not hydrophobically modified.
[0030] As used herein, the term "crosslinked (co)polymer" of the present invention refers to a crosslinked anionic polyelectrolyte made from ethylenically unsaturated monomers. Specifically, it is a crosslinked derivative of a linear non-crosslinked (co)polymer as described above. Crosslinking can be achieved by various techniques known to those skilled in the art, such as copolymerization with multifunctional ethylenically unsaturated monomers or post-polymerization reaction to induce crosslinking. Examples include, but are not limited to, carbomers and acrylate crosslinked polymers. An example of a carbomer is available from Lubrizol, Inc. 934, 940, 980, ULTREZ10, ULTREZ30, ETD2050, 2984 or from Ashland, Inc. 940, 941, 980, 981. An example of an acrylate crosspolymer is acrylate crosspolymer-4 (available from Lubrizol, Inc. Aqua SF-2). Other examples include superabsorbent polymers, i.e., cross-linked sodium polyacrylate particles.
[0031] As used herein, the term "hydrophobically modified (co)polymer" refers to linear non-crosslinked and crosslinked (co)polymers comprising hydrophobic monomers. Specifically, "hydrophobically modified" refers to polyelectrolytes containing some amount of monomers containing hydrophobic side groups (hydrophobic monomers, or associative monomers). Typically, the amount of monomers containing hydrophobic side groups is from about 0.1 wt % to about 20 wt %, more typically from about 0.5 wt % to about 10 wt %, and even more typically from about 1 wt % to about 5 wt %. They may optionally contain a crosslinking agent and / or may optionally be a crosslinked (co)polymer. An example is an acrylate / C10-30 alkyl acrylate crosslinked polymer (available from Lubrizol, Inc. ETD2020, Ultrez 20) and acrylates / vinyl isodecanate crosspolymer (Stabylen 30 from 3V Sigma, Inc.).
[0032] As used herein, "non-hydrophobically modified" means that the polyelectrolyte contains no or only a small amount of monomers containing hydrophobic side groups (hydrophobic monomers, or associative monomers). Typically, the amount of monomers containing hydrophobic side groups is about 1 wt% or less, more typically about 0.5 wt% or less, and even more typically about 0.1 wt% or less. The exception is a crosslinker monomer / molecule, which may have a side chain of greater than 4 carbon atoms, but is not considered a hydrophobic monomer (and its use level in the polyelectrolyte is generally low, i.e., less than 1 wt%).
[0033] As used herein, the term "alkali-swellable emulsion polymer" or "ASE polymer" refers to a polyelectrolyte made from ethylenically unsaturated monomers, such as acrylate or vinyl (co)polymers, and wherein the polymer comprises anionizable monomers such that upon addition of a base it becomes ionized and swells and / or dissolves in aqueous solution. The ASE polymer may optionally comprise a crosslinker and / or may optionally be a crosslinked polymer (xASE). In one embodiment, the ASE or xASE polymer is an acrylate (co)polymer consisting of one or more (meth)acrylic acid monomers and / or one of their simple alkyl esters (including methyl, ethyl, propyl, butyl), simple hydroxyalkyl esters (including hydroxyethyl, hydroxybutyl) and simple alkoxyalkyl esters (including methoxyethyl, ethoxyethyl). "Simple" alkyl esters refer to alkyl groups having 1 to 4 carbon atoms. The amount of the simple alkyl (meth)acrylate monomer in the polymer is in the range of 0-80 wt%, 10 wt%-70 wt%, 20 wt%-70 wt%, 30 wt%-70 wt%, 30 wt%-60 wt%. Specific examples of the simple alkyl (meth)acrylate monomer include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, methoxyethyl (meth)acrylate, ethoxyethyl (meth)acrylate. Examples of ASE polymers are acrylate copolymers (e.g., available from Lubrizol, Inc. Aqua SF-1 or Eliclear from Seppic, Inc. TM 4U) or potassium acrylate copolymer (EX-968 and EX-1112 from Lubrizol, Inc.).
[0034] As used herein, the term "hydrophobically modified alkali-swellable emulsion polymer" or "HASE polymer" (including "xHASE polymer") refers to an ASE polymer and an xASE polymer, respectively, that comprises a hydrophobic monomer (see definition of "hydrophobically modified" above). An example of a HASE polymer is polyacrylate-33 (Rheomer available from Solvay, Inc. TM 33), and an example of xHASE is, for example, acrylates / steareth-20 methacrylate crosspolymer (Aculyn 88 from Dow, Inc. TM ).
[0035] Hydrophobic monomers (also referred to as "associative" monomers) used in hydrophobically modified polyelectrolytes are described, for example, in U.S. Pat. No. 5,292,843, U.S. Pat. No. 6,897,253, U.S. Pat. No. 7,288,616, U.S. Pat. No. 3,035,004, and U.S. Patent Publication No. 2006 / 0270563, the contents of each of which are hereby incorporated by reference in their entirety.
[0036] As used herein, the term "non-crosslinked" refers to a (co)polymer that contains substantially no covalent bonds between polymer chains.
[0037] As used herein, the term "crosslinking" refers to a (co)polymer having some amount of covalent bonds between polymer chains. Such bonds are generated by adding some amount of crosslinking monomers to the (co)polymer during the polymerization process. Examples of crosslinking agents are allyl ethers of pentaerythritol, allyl ethers of sucrose or allyl ethers of propylene, or trimethylolpropane triacrylate, ethylene glycol dimethacrylate. Additional crosslinking agents are described in U.S. Pat. No. 9,187,590 B2, the contents of which are incorporated herein by reference.
[0038] Anionic polyelectrolytes derived from ethylenically unsaturated monomers may also contain other monomers. For example, vinyl esters (such as vinyl acetate, vinyl propionate), N-vinyl amides (such as N-vinyl pyrrolidone, N-vinyl caprolactam, N-vinyl formamide and N-vinylacetamide), vinyl ethers (such as methyl vinyl ether, ethyl vinyl ether, butyl vinyl ether and hydroxybutyl vinyl ether), ethylenically unsaturated aromatic compounds (such as styrene, acetoxyethyl (meth) acrylate), (meth) acrylamides (such as (meth) acrylamide, dimethyl acrylamide, N-hydroxymethyl (meth) acrylamide, N-butoxyethyl (meth) acrylamide, N,N-dimethyl (meth) acrylamide, N-isopropyl (meth) acrylamide, N-tert-butyl (meth) acrylamide) and ethylenically unsaturated alkyl esters of dicarboxylic acid monomers (such as butyl methyl maleate).
[0039] Anionic and anionically modified polysaccharides and polysaccharide derivatives include, but are not limited to:
[0040] a. Naturally occurring anionic polysaccharides: alginate (alginic acid), pectin, carrageenan, xanthan gum, hyaluronic acid, chondroitin sulfate, gum arabic, gum karaya, gum tragacanth, arabinoxylan, heparan sulfate, and
[0041] b. Anionically modified polysaccharides: including starches, gums, celluloses (such as carboxymethyl starch, starch phosphates, hydroxypropyl starch phosphates, starch sulfates, starch-2-hydroxypropyl citrate, carboxymethyl guar gum, carboxymethyl hydroxypropyl guar gum, other anionic galactomannan derivatives, carboxymethyl cellulose (INCI name: cellulose gum, for example Aqualon TM Sodium CMC is available from Ashland, Inc. or as Walocel TM CRT is available from Dow, Inc.), polyanionic cellulose, cellulose sulfate, cellulose phosphate, and carboxyethyl cellulose, as well as other polysaccharides such as dextran and dextrin, such as dextran / dextrin sulfate.
[0042] Other anionic polyelectrolytes include anionic / anionizable proteins, anionic polypeptides (eg, polyglutamic acid, polyaspartic acid), and other anionic copolymers (eg, polynucleic acids).
[0043] Cationic polyelectrolyte
[0044] Cationic polyelectrolytes are polymers with multiple cationic charges, i.e., the polyelectrolytes contain repeating units with cationic moieties. Cationic polyelectrolytes suitable for use in the compositions of the present invention contain cationic nitrogen-containing moieties, such as quaternary ammonium or cationic protonated amino moieties. The cationic protonated amines may be primary, secondary or tertiary amines (preferably secondary or tertiary amines), depending on the particular species and selected pH of the composition. Any anionic counterions may be used in combination with cationic polyelectrolytes, as long as the polyelectrolyte remains soluble in water, the composition or the coacervate phase of the composition, and as long as the counterions are physically and chemically compatible with the major components of the composition, or do not unduly impair the performance, stability or aesthetics of the product. Non-limiting examples of such counterions include halides (e.g., chlorides, fluorides, bromides, iodides), sulfates, methylsulfates and ethylsulfates, citrates, acetates and lactates.
[0045] The compositions of the present invention comprise from about 0.1% to about 1% by weight of a cationic polyelectrolyte, more preferably from about 0.1% to about 0.8% by weight.
[0046] In the pH range intended for use in the compositions of the present invention, the cationic charge density of the preferred cationic polyelectrolytes used in the compositions is at least about 0.2 meq / g, preferably at least about 0.6 meq / g, more preferably at least about 1.5 meq / g, but also preferably less than about 7 meq / g, more preferably less than about 5 meq / g, and even more preferably less than about 3 meq / g. As used herein, the "cationic charge density" of a polyelectrolyte refers to the ratio of the number of positive charges on the polyelectrolyte to the molecular weight of the polyelectrolyte. Such suitable cationic polyelectrolytes will typically have a weight average molecular weight (Mw) between about 10,000 and about 5 million g / mol, preferably between about 50,000 and about 5 million g / mol, more preferably between about 100,000 and about 3 million g / mol. The cationic polyelectrolyte may be a crosslinked (co)polymer.
[0047] Non-limiting examples of such cationic polyelectrolytes are described in the International Cosmetic Ingredient Dictionary and Handbook, 15, published by the Personal Care Products Council (PCPC), Washington DC. th The contents of the corresponding INCI monograph in 2004-06-08 are incorporated herein by reference.
[0048] Non-limiting examples of suitable cationic polyelectrolytes include copolymers of ethylenically unsaturated monomers having cationic protonated amine or quaternary ammonium functional groups and water-soluble spacer monomers such as acrylamide, methacrylamide, alkyl and dialkyl acrylamides, alkyl and dialkyl methacrylamides, alkyl acrylates, alkyl methacrylates, vinyl caprolactone, or vinyl pyrrolidone.
[0049] Suitable cationic protonated amino and quaternary ammonium monomers for inclusion in the cationic polyelectrolytes of the compositions herein include ethylenically unsaturated compounds substituted with dialkylaminoalkyl acrylates, dialkylaminoalkyl methacrylates, monoalkylaminoalkyl acrylates, monoalkylaminoalkyl methacrylates, trialkylmethacryloyloxyalkylammonium salts, trialkylacryloyloxyalkylammonium salts, diallyl quaternary ammonium salts, and vinyl quaternary ammonium monomers having cyclic cationic nitrogen-containing rings such as pyridinium, imidazolium, and quaternized pyrrolidones, for example, alkylvinylimidazolium, alkylvinylpyridinium, alkylvinylpyrrolidone salts.
[0050] Other suitable cationic polyelectrolytes for use in the composition include copolymers of 1-vinyl-2-pyrrolidone and 1-vinyl-3-methylimidazolium salt (e.g., chloride salt) (INCI name: POLYQUATERNIUM-16); copolymers of 1-vinyl-2-pyrrolidone and dimethylaminoethyl methacrylate (INCI name: POLYQUATERNIUM-11); copolymers of vinyl pyrrolidone and quaternized vinyl imidazolium salt (INCI name: POLYQUATERNIUM-44); copolymers of vinyl pyrrolidone and methacrylamidopropyltrimonium chloride (INCI name: POLYQUATERNIUM-28); copolymers of methacryloyloxyethyltrimethylammonium methylsulfate (METAMS) and acrylamide (INCI name: POLYQUATERNIUM- Salt-5); quaternary ammonium-containing cationic diallyl polymers, including, for example, dimethyldiallylammonium chloride homopolymers, copolymers of acrylamide and dimethyldiallylammonium chloride (INCI names: Polyquaternium-6 and Polyquaternium-7, respectively); amphoteric copolymers of acrylic acid, including copolymers of acrylic acid and dimethyldiallylammonium chloride (INCI name: Polyquaternium-22); polyampholyte (co)polymers, such as polybetaines and polysulfobetaines, terpolymers of acrylic acid with dimethyldiallylammonium chloride and acrylamide (INCI name: Polyquaternium-39), and terpolymers of acrylic acid with methacrylamidopropyltrimonium chloride and methacrylate (INCI name: Polyquaternium-47). Preferred cationic substituted monomers are cationic substituted dialkylaminoalkyl acrylamides, dialkylaminoalkyl methacrylamides, and combinations thereof. A non-limiting specific example is polymethacrylamidopropyltrimethylammonium chloride. Also preferred are copolymers of cationic monomers with nonionic monomers such that the charge density of the total copolymer is from about 0.6 to about 5 meq / g.
[0051] Other suitable cationic polyelectrolytes for use in the composition include polysaccharide polymers, such as cationic cellulose derivatives and cationic starch derivatives. Suitable cationic polysaccharide polymers include those that conform to the following formula:
[0052]
[0053] wherein A is an anhydroglucose residue, such as starch or cellulose anhydroglucose residue; R is an alkylene oxide, polyoxyalkylene or hydroxyalkylene, or a combination thereof; R1, R2 and R3 are independently alkyl, aryl, alkaryl, aralkyl, alkoxyalkyl or alkoxyaryl, each group containing up to about 18 carbon atoms, and the total number of carbon atoms in each cationic portion (i.e., the sum of carbon atoms in R1, R2 and R3) is preferably about 20 or less, more preferably about 10 or less; and X is an anionic counterion as described above. In a preferred embodiment, R is 2-hydroxypropyl, and R1, R2 and R3 are methyl.
[0054] A preferred cationic cellulose polymer is the salt of hydroxyethylcellulose reacted with a trimethylammonium-substituted epoxide (INCI name: Polyquaternium-10). Other suitable types of cationic cellulose include polyquaterniums of hydroxyethylcellulose reacted with a lauryldimonium-substituted epoxide (INCI name: Polyquaternium-24) and polyquaterniums reacted with lauryldimonium and trimethylammonium-substituted epoxides (INCI name: Polyquaternium-67).
[0055] Other suitable cationic polyelectrolytes include cationic galactomannans, such as cationic tara gum, cassia gum, and guar gum derivatives, such as guar hydroxypropyltrimonium chloride, specific examples of which include the Jaguar series commercially available from Solvay, Inc. and the N-Hance series commercially available from Ashland, Inc. Other suitable cationic polyelectrolytes include quaternary nitrogen-containing cellulose ethers, some examples of which are described in U.S. Pat. No. 3,962,418, which is incorporated herein by reference. Other suitable cationic polyelectrolytes include copolymers of etherified cellulose, guar, and starch, some examples of which are described in U.S. Pat. No. 3,958,581, the contents of which are incorporated herein by reference. Other suitable conditioning polymers include those disclosed in U.S. Pat. No. 5,876,705, the contents of which are incorporated herein by reference. When used, the cationic polyelectrolytes herein are soluble in the composition, or are soluble in the complex coacervate phase of the composition formed by the aforementioned cationic polyelectrolyte and anionic, amphoteric and / or zwitterionic cleansing surfactant components.
[0056] Other suitable cationic polyelectrolytes may include proteins with a cationic charge such as gelatin, ovalbumin, serum albumin, casein, and hydrolyzed wheat or rice or silk proteins substituted with hydroxypropyltrimethylammonium moieties and cationic polypeptides such as poly(L-lysine), poly(L-arginine), abaecin, propenin, or indolicidin.
[0057] Other suitable cationic polyelectrolytes include linear and branched polyethyleneimine (PEI) (co)polymers. Examples include PEI-2500, PEI-14M.
[0058] Generally, it is recognized that cationic polyelectrolytes exist in cleaning compositions as a coacervate phase, or form a coacervate phase upon dilution. If not already present as a coacervate in the cleaning composition, the cationic polyelectrolyte will preferably exist in the cleaning composition as a complex coacervate upon dilution with water to a water to composition weight ratio of about 20: 1, more preferably about 10: 1, even more preferably about 5: 1, and even more preferably about 3: 1.
[0059] Surfactants
[0060] The compositions of the present invention comprise from about 1 wt % to about 25 wt % of a surfactant, more preferably from about 3 wt % to about 25 wt % of a surfactant, more preferably from about 3 wt % to about 15 wt %, even more preferably from about 3 wt % to about 12 wt %, even more preferably from about 4 wt % to about 12 wt %.
[0061] Suitable surfactants may be anionic, zwitterionic, nonionic and cationic surfactants, examples of which are described below.
[0062] As used herein, the term "anionic surfactant" refers to a surfactant that has at least a negative charge and does not carry a counter ion (M). + ) are positively charged surfactant molecules other than . Suitable anionic surfactants include those selected from the following classes of surfactants:
[0063] ·Acyl isethionate
[0064]
[0065] Where RCO = C8-C 20 Acyl (straight or branched, saturated or unsaturated) or mixtures thereof, R'=H or CH3, M + = monovalent cation, such as sodium cocoyl isethionate (RCO = cocoyl, R' = H, M + =Na + ) and sodium lauroyl methyl isethionate (RCO = lauroyl, R' = CH3, M + =Na + ).
[0066] ·Alkyl sulfosuccinate
[0067]
[0068] Where R = C8-C 20 alkyl (linear or branched, saturated or unsaturated) or a mixture thereof, and M + = monovalent cation, such as disodium lauryl sulfosuccinate (R = lauryl, M + =Na + ).
[0069] ·α-sulfo fatty acid esters
[0070]
[0071] Where R = C6-C 16Alkyl (linear or branched, saturated or unsaturated) or a mixture thereof, R' = C1-C2 alkyl, and M + = monovalent cation, such as sodium methyl 2-sulfolaurate (R = C- 10 H 21 , R'=methyl, CH3-, M + =Na + );
[0072] ·α-sulfonated fatty acid salts
[0073]
[0074] Where R = C6-C 16 Alkyl (straight or branched, saturated or unsaturated) or mixtures thereof, M + = monovalent cation, such as disodium 2-sulfolaurate (R = C 10 H 21 ,
[0075] M + =Na + );
[0076] Alkyl sulfoacetate
[0077]
[0078] Where R = C6-C 18 Alkyl (straight or branched, saturated or unsaturated) or mixtures thereof, M + = monovalent cation, such as sodium lauryl sulfoacetate (R = lauryl,
[0079] C 12 H 25 , M + =Na + ).
[0080] Alkyl sulfate
[0081]
[0082] Where R = C8-C 20 Alkyl (linear or branched, saturated or unsaturated) or mixtures thereof. Specific examples include TEA lauryl sulfate (R = lauryl, C 12 H 25 , M + = + HN(CH2CH 2- OH)3), sodium lauryl sulfate (R = lauryl, C 12 H 25 ,
[0083] M + =Na + ) and sodium cocoyl sulfate (R = coconut oil alkyl, M + =Na + ).
[0084] Alkyl glyceryl ether sulfonate or alkoxy hydroxypropyl sulfonate:
[0085]
[0086] Where R = C8-C 24 alkyl (linear or branched, saturated or unsaturated) or a mixture thereof, and M + = monovalent cation, such as sodium cocoglyceryl ether sulfonate (R = coconut alkyl, M + =Na + );
[0087] α-Olefin sulfonates (AOS) prepared by sulfonation of long chain α-olefins. α-Olefin sulfonates consist of a mixture of: olefin sulfonates,
[0088]
[0089] Where R = C4-C 18 alkyl or a mixture thereof, and M + =monovalent cations, and hydroxyalkyl sulfonates,
[0090]
[0091] Where R = C4-C 18 alkyl or a mixture thereof, and M + = monovalent cation. Examples include sodium C12-14 olefin sulfonate (R = C8-C 10 Alkyl, M + =Na + ) and sodium C14-16 olefin sulfonate (R = C 10 -C 12 Alkyl, M + =Na + );
[0092] Alkyl sulfonate or paraffin sulfonate:
[0093]
[0094] Where R = C8-C 24 alkyl (linear or branched, saturated or unsaturated) or a mixture thereof, and M + = monovalent cation. Examples include sodium C13-17 alkane sulfonate (R = C13 -C 17 Alkyl, M + =Na + ) and sodium C14-17 secondary alkyl sulfonate (R = C 14 -C 17 Alkyl, M + =Na + );
[0095] Alkyl aryl sulfonate or linear alkyl benzene sulfonate
[0096]
[0097] Where R = C6-C 18 alkyl (linear, saturated or unsaturated) or a mixture thereof, and M + = monovalent cation. Examples include Sodium Deceylbenzenesulfonate (R = C 10 Alkyl, M + =Na + ) and ammonium dodecylbenzenesulfonate (R=C 12 Alkyl, M + =NH4 + );
[0098] ·Alkyl ether sulfate
[0099]
[0100] Where R = C8-C 24 Alkyl (linear or branched, saturated or unsaturated) or a mixture thereof, n = 1-12, and M + = monovalent cation. Examples include sodium laureth sulfate (R = C 12 Alkyl, M + =Na + , n = 1-3), ammonium lauryl polyoxyethylene ether sulfate (R = C 12 Alkyl, M + =NH4 + , n = 1-3) and sodium tridecyl polyoxyethylene ether sulfate (R = C 13 Alkyl, M + =Na + , n=1-4);
[0101] Alkyl monoglyceride sulfate
[0102]
[0103] Where RCO = C8-C 24acyl (straight chain or branched chain, saturated or unsaturated) or a mixture thereof, and M + = monovalent cation. Examples include sodium cocoyl monoglyceride sulfate (RCO = cocoyl, M + =Na + ) and ammonium cocoyl monoglyceride sulfate (RCO = cocoyl, M + =NH4 + );
[0104] ·Alkyl ether carboxylates
[0105]
[0106] Where R = C8-C 24 Alkyl (linear or branched, saturated or unsaturated) or a mixture thereof, n = 1-20, and M + = monovalent cation. Examples include sodium laureth-13 carboxylate (R = C 12 Alkyl, M + =Na + , n = 13) and sodium laureth-3 carboxylate (R = C 12 Alkyl, M + =Na + , n=3);
[0107] ·Alkyl ether sulfosuccinate
[0108]
[0109] Where R = C8-C 20 Alkyl (linear or branched, saturated or unsaturated) or a mixture thereof, n = 1-12, and M + = monovalent cation, such as disodium laureth sulfosuccinate (R = lauryl, n = 1-4, and M + =Na + )
[0110] ·Dialkyl sulfosuccinate
[0111]
[0112] Where R = C6-C 20 alkyl (linear or branched, saturated or unsaturated) or a mixture thereof, and M + = monovalent cation, such as sodium diethylhexyl sulfosuccinate (R = 2-ethylhexyl, M + =Na + ).
[0113] ·Alkylamidoalkyl sulfosuccinate
[0114]
[0115] Where R = C8-C 20 alkyl (linear or branched, saturated or unsaturated) or a mixture thereof, R' = C-2-C4 alkyl (linear or branched), and M + = monovalent cation, such as disodium cocamide MIPA sulfosuccinate (RCO = cocoyl, R' = isopropyl, M + =Na + ).
[0116] ·Alkyl sulfosuccinamide salt
[0117]
[0118] Where R = C8-C 20 alkyl (linear or branched, saturated or unsaturated) or a mixture thereof, and M + = monovalent cation, such as disodium stearyl sulfosuccinamate (R = stearyl, C 18 H 37 , M + =Na + ).
[0119] Acylglutamate
[0120]
[0121] Where RCO = C6-C 20 Acyl (straight or branched, saturated or unsaturated) or mixtures thereof, R'=H or CH3, M + = monovalent cation, such as disodium cocoyl glutamate (RCO = cocoyl, R' = H, M + =Na + ) and disodium lauroyl glutamate (RCO = lauroyl, R' = H, M + =Na + ).
[0122] ·Acyl aspartate
[0123]
[0124] Where RCO = C6-C 20 Acyl (straight or branched, saturated or unsaturated) or mixtures thereof, R'=H or CH3, M + = monovalent cation, such as disodium N-lauroyl aspartate (RCO = lauroyl, R' = H, M + =Na + ).
[0125] Acyl Taurates
[0126]
[0127] Where RCO = C6-C 20 Acyl (straight or branched, saturated or unsaturated) or mixtures thereof, R'=H or CH3, M + = monovalent cation, such as sodium methyl cocoyl taurate (RCO = cocoyl, R' = CH3, M + =Na + ) and sodium cocoyl taurate (RCO = lauroyl, R' = H, M + =Na + ).
[0128] Acyl lactylate
[0129]
[0130] Where RCO = C8-C 20 Acyl (straight or branched chain, saturated or unsaturated) or mixtures thereof, M + = monovalent cation, such as sodium lauroyl lactylate (RCO = lauroyl, M + =Na + ).
[0131] Acyl glycinates and acyl sarcosinates
[0132]
[0133] Where RCO = C8-C 20 Acyl (straight or branched chain, saturated or unsaturated) or mixtures thereof, R'=H (glycinate) or CH3 (sarcosinate), M + = monovalent cation, such as sodium cocoyl glycinate (RCO = cocoyl, R' = H, M + =Na + ), ammonium cocoyl sarcosinate (RCO = cocoyl, R' = CH3, M + =NH4 + ) and sodium lauroyl sarcosinate (RCO = lauroyl, R' = CH3, M + =Na + ).
[0134] Anionic derivatives of alkyl polyglucosides include: sodium lauryl glucoside carboxylate, disodium coco-glucoside citrate, sodium coco-glucoside tartrate, disodium coco-glucoside sulfosuccinate; sodium coco-glucoside hydroxypropyl sulfonate, sodium decyl glucoside hydroxypropyl sulfonate, sodium lauryl glucoside hydroxypropyl sulfonate; sodium hydroxypropyl coco-glucoside sulfonate crosspolymer, sodium hydroxypropyl decyl glucoside sulfonate crosspolymer, sodium hydroxypropyl lauryl glucoside sulfonate crosspolymer; anionic polymeric APG derivatives such as those described by O'Lenick in U.S. Pat. Nos. 7,507,399, 7,375,064 and 7,335,627; and combinations of two or more thereof, and the like.
[0135] As used herein, the term "sulfated anionic surfactant" refers to an anionic surfactant containing -SO4 - M + Anionic surfactants of the group, where M + Does not exist or is H + or NH4 + Or Na + or K + Or other monovalent or multivalent anions. Examples of sulfated anionic surfactants include, but are not limited to, sodium lauryl sulfate and sodium laureth sulfate. In certain embodiments, the composition of the present invention is substantially free of sulfated anionic surfactants, preferably free of sulfated anionic surfactants.
[0136] In certain embodiments, the compositions of the present invention are substantially free of anionic surfactants, and preferably free of anionic surfactants.
[0137] In certain embodiments of the present invention, the composition may include a zwitterionic surfactant. Suitable concentrations of zwitterionic surfactants are about 0 wt % to 15 wt %, preferably about 1 wt % to 10 wt %, more preferably about 2 wt % to 6 wt %.
[0138] In certain embodiments, the compositions of the present invention contain one or more anions and one or more zwitterionic surfactants. The weight ratio of anions to one or more zwitterionic surfactants in the composition may range from 1:0 to 0:1. A typical range of anions: zwitterions is 4:1 to 1:4.
[0139] As used herein, "zwitterionic surfactants" refer to amphiphilic molecules comprising a hydrophobic group and one or more hydrophilic groups, wherein the hydrophilic group comprises two moieties that are oppositely charged or capable of generating oppositely charged moieties (depending on the acidity and alkalinity and solution pH). Sometimes, such surfactants are also referred to as "amphoteric surfactants".
[0140] Suitable zwitterionic surfactants include, but are not limited to, those described by the following formula:
[0141] as well as Wherein R1 is a linear, branched, saturated or unsaturated C5 to C21 hydrophobic group;
[0142] R2 is a linear, branched or cyclic alkyl, hydroxyalkyl or aromatic group;
[0143] R3 is a straight or branched alkyl, hydroxyalkyl or aromatic group;
[0144] R4 is a straight or branched alkyl, hydroxyalkyl or aromatic group;
[0145] R5 is a linear or branched alkyl, hydroxyalkyl or aromatic group; and
[0146] Any of R2, R4 or R5 may be connected via a ring structure; and
[0147] Y is -N(H)-, -N(R3)-, -O-, -S-; and
[0148] X is -CO2-, -SO3- or -SO4- or a phosphate or phosphonate group.
[0149] Examples of zwitterionic surfactants include:
[0150] Alkylamidoalkylbetaine represented by the following formula:
[0151]
[0152] Where RCO = C6-C 24 Acyl (saturated or unsaturated) or mixtures thereof, and x = 1 to 4. Examples include cocamide ethyl betaine (RCO = cocoyl, x = 2), cocamide propyl betaine (RCO = cocoyl, x = 3), lauramidopropyl betaine (RCO = lauroyl, and x = 3), myristamidopropyl betaine (RCO = myristoyl, and x = 3), soya amidopropyl betaine (R = soya acyl, x = 3) and oleamidopropyl betaine (RCO = oleoyl, and x = 3).
[0153] Alkylamidoalkylhydroxysulfonyl betaine represented by the following formula:
[0154]
[0155] Where RCO = C6-C 24Acyl (saturated or unsaturated) or mixtures thereof. Examples include cocamidopropyl hydroxysultaine (RCO=cocoyl, x=3), lauramidopropyl hydroxysultaine (RCO=lauroyl, and x=3), myristamidopropyl hydroxysultaine (RCO=myristoyl, and x=3) and oleamidopropyl hydroxysultaine (RCO=oleoyl, and x=3).
[0156] Alkylamidoalkylsulfonobetaine represented by the following formula:
[0157]
[0158] Where RCO = C6-C 24 Acyl (saturated or unsaturated) or mixtures thereof. Examples include cocamidopropyl sultaine (RCO=cocoyl, x=3), lauramidopropyl sultaine (RCO=lauroyl, and x=3), myristamidopropyl sultaine (RCO=myristoyl, and x=3), soyaamidopropyl betaine (RCO=soyacyl, x=3) and oleamidopropyl betaine (RCO=oleoyl, and x=3).
[0159] Amphoteric acetate represented by the following formula:
[0160]
[0161] Where RCO = C6-C 24 acyl (saturated or unsaturated) or a mixture thereof, and M + = monovalent cation. Examples include sodium lauroyl amphoacetate (RCO = lauroyl, and M + =Na + ) and sodium cocoamphoacetate (RCO = cocoyl, and M + =Na + ).
[0162] Amphoteric diacetates represented by the following formula:
[0163]
[0164] Where RCO = C6-C 24 acyl (saturated or unsaturated) or a mixture thereof, and M + = monovalent cation. Examples include disodium lauroamphodiacetate (RCO = lauroyl, and M = Na + ) and disodium cocoamphodiacetate (RCO = cocoyl, and M = Na + ).
[0165] Amphoteric propionate represented by the following formula:
[0166]
[0167] Where RCO = C6-C 24 acyl (saturated or unsaturated) or a mixture thereof, and M + = monovalent cation. Examples include sodium lauroylamphopropionate (RCO = lauroyl, and M + =Na + ) and sodium cocoamphopropionate (RCO = cocoyl, and M + =Na + ).
[0168] Amphoteric dipropionate represented by the following formula:
[0169]
[0170] Where RCO = C6-C 24 acyl (saturated or unsaturated) or a mixture thereof, and M + = monovalent cation. Examples include disodium lauroylamphodipropionate (RCO = lauroyl, and M + =Na + ) and disodium cocoamphodipropionate (RCO = cocoyl, and M + =Na + ).
[0171] Amphoteric isopropyl sulfonate represented by the following formula:
[0172]
[0173] Where RCO = C6-C 24 Acyl (saturated or unsaturated) or a mixture thereof, M + = monovalent cation, such as sodium lauroyl amphohydroxypropyl sulfonate (RCO = lauroyl, and M + =Na + ) and sodium cocoyl amphohydroxypropyl sulfonate (RCO = cocoyl, and M + =Na + ).
[0174] Other examples include amphoteric hydroxyalkyl phosphates and alkylamidoalkylamine oxides.
[0175] In certain embodiments of the present invention, the composition may include a nonionic surfactant. Suitable concentrations of nonionic surfactants are from about 0% by weight to about 15% by weight, typically from about 1% by weight to 10% by weight, and more typically from about 2% by weight to about 6% by weight. As used herein, the term "nonionic surfactant" refers to a surfactant molecule that is not electrostatically charged. Any of a variety of nonionic surfactants is suitable for use in the present invention. Examples of suitable nonionic surfactants include, but are not limited to, fatty alcohol acid or amide ethoxylates, monoglyceride ethoxylates, sorbitan ester ethoxylates, alkyl polyglucosides, mixtures thereof, and the like. Certain preferred nonionic surfactants include polyethyleneoxy derivatives of polyol esters, wherein the polyethyleneoxy derivative of polyol ester (1) is derived from (a) a fatty acid containing from about 8 to about 22, preferably from about 10 to about 14 carbon atoms, and (b) a polyol selected from sorbitol, sorbitan, glucose, α-methyl glucoside, polyglucose having an average of about 1 to about 3 glucose residues per molecule, glycerol, pentaerythritol, and mixtures thereof; (2) contains an average of about 10 to about 120, preferably from about 20 to about 80 ethyleneoxy units; and (3) has an average of about 1 to about 3 fatty acid residues per mole of the polyethyleneoxy derivative of polyol ester. Examples of such preferred polyethyleneoxy derivatives of polyol esters include, but are not limited to, PEG-80 sorbitan laurate and polysorbate 20. PEG-80 sorbitan laurate is a sorbitan monoester of lauric acid ethoxylated with an average of about 80 moles of ethylene oxide. Polysorbate 20 is the monolauric acid ester of a mixture of sorbitol and sorbitan condensed with approximately 20 moles of ethylene oxide.
[0176] Another class of suitable nonionic surfactants includes long chain alkyl glucosides or polyglucosides which are condensation products of (a) long chain alcohols containing from about 6 to about 22 carbon atoms, preferably from about 8 to about 14 carbon atoms, and (b) glucose or a glucose-containing polymer. Preferred alkyl glucosides contain from about 1 to about 6 glucose residues per molecule of the alkyl glucosides. A preferred glucoside is decyl glucoside which is the condensation product of decanol and a glucose oligomer.
[0177] Another class of suitable nonionic surfactants are polyglycerol nonionic surfactants. Examples of polyglycerol nonionic surfactants include, but are not limited to, polyglycerol esters (PGE), such as polyglyceryl-10 laurate.
[0178] As used herein, the term "polyglyceryl nonionic surfactant" refers to an amphiphilic molecule comprising one or more nonionic hydrophilic segments consisting of a polyglyceryl moiety and one or more hydrophobic moieties. Examples of polyglyceryl nonionic surfactants include, but are not limited to, polyglyceryl esters (PGE), such as polyglyceryl-10 laurate, wherein PG = a polyglyceryl moiety comprising ten (10) glyceryl repeating units, R = C 11 H 23 :
[0179]
[0180] As well as polyglyceryl-10 caprylate / caprate, polyglyceryl-10 cocoate, polyglyceryl-10 myristate, polyglyceryl-10 palmitate, polyglyceryl-10 oleate, polyglyceryl-12 laurate, etc. The PGE of the present invention may contain a polyglyceryl moiety with multiple ester substitutions (i.e., the PGE may be a monoester, diester, triester, etc.). Other polyglyceryl nonionic surfactants include polyglyceryl ethers, such as polyglyceryl-10 lauryl ether, where PG = a polyglyceryl moiety containing 10 glyceryl repeating units, R = C 12 H 25 :
[0181]
[0182] Etc. Other polyglyceryl nonionic surfactants include polyglycerol sorbitan fatty acid esters, such as polyglyceryl-20 sorbitan laurate, where PG = polyglycerol, the sum of all PG repeating units = 20, and R = C11H23. (See Bevinakatti et al., WO 2009016375 assigned to Croda International PLC)
[0183]
[0184] Another class of suitable nonionic surfactants includes the alkanolamides, such as cocamide MEA and cocamide DEA.
[0185] In certain embodiments of the present invention, the composition may also include an inorganic salt. Suitable inorganic salts for use in the present invention include, but are not limited to, sodium chloride, potassium chloride, sodium bromide, potassium bromide, ammonium chloride, ammonium bromide, and other salts containing monovalent and multivalent ions. Typically, the composition of the present invention will include about 0.05% by weight to about 6% by weight of an inorganic salt, or about 0.1% by weight to about 4% by weight of an inorganic salt, or about 0.1% by weight to about 2% by weight of an inorganic salt, or about 0.1% by weight to about 1.5% by weight of an inorganic salt.
[0186] In certain embodiments of the present invention, the composition may also include a cationic surfactant. Suitable cationic surfactants for use in the present invention include, but are not limited to, alkyl quaternary salts (monoalkyl quaternary salts, dialkyl quaternary salts or trialkyl quaternary salts), benzyl quaternary salts, ester-type quaternary salts, ethoxylated quaternary salts, alkylamines, and mixtures thereof, wherein the alkyl group has from about 6 carbon atoms to about 30 carbon atoms, wherein from about 8 to about 22 carbon atoms are preferred.
[0187] Composition of the present invention can also comprise any other composition or additive that is generally used in personal care products (for example, skin care products) or cosmetic preparations, including active ingredient.Other composition or the example of additive are surfactant, emulsifier, viscosity control agent, lubricant, chelating agent, filler, cement, antioxidant, preservative and preservative aid, dye, buffer, pH adjusting agent, solvent and beneficial agent (such as active ingredient, spices, exfoliating particles, emollient, humectant, wetting agent, pigment and sunscreen etc.), and the prerequisite is that they are physically and chemically compatible with other components of composition.Active ingredient can include but is not limited to anti-inflammatory agent, antibacterial agent, antifungal agent, antipruritic agent, humectant, plant extract, vitamin etc.Also comprise sunscreen active substance, its character can be inorganic or organic.
[0188] The compositions of the present invention may also contain thickeners, suspending agents and rheology modifiers which are not part of the "polyelectrolyte conditioning system". Examples include, but are not limited to: a) polysaccharides of natural origin, including Cyamopsistetragonoloba (guar) gum, cassia gum, microcrystalline cellulose, ethoxylated and non-ethoxylated derivatives of cellulose (e.g., hydroxyethyl and hydroxypropyl methylcellulose, etc.), and hydroxypropyl guar gum; b) synthetic polymers, including acrylate polymers, such as surfactant reactive microgels (e.g., as described in U.S. Pat. No. 9,096,755 B2, examples include acrylates / beheneth-25 methacrylate / HEMA crosspolymer and acrylates / c) micellar thickeners such as cocamide MIPA, lauryl lactylate or sorbitan sesquioctanoate or polyethylene glycol-based thickeners (such as PEG-150 distearate and PEG-120 methyl glucose dioleate and trioleate); and d) other thickeners such as silicones, waxes, clays, silica, salts, natural and synthetic esters, or fatty alcohols; and e) combinations of two or more thereof, and the like.
[0189] Examples of preservatives and preservative aids include, but are not limited to, organic acids (e.g., benzoic acid, lactic acid, salicylic acid), benzyl alcohol, 1,2-octanediol, decanediol, ethylhexylglycerin, gluconolactone, methylisothiazolinone, combinations of two or more thereof, and the like.
[0190] The composition of the present invention may contain dispersed insoluble particles. The dispersed particles may be beneficial agents such as oil droplets, zinc pyrithione particles, mica particles, colloidal oatmeal and crushed walnut shells. In the composition of the present invention, preferably at least 0.025% by weight of dispersed particles are incorporated, more preferably at least 0.05% by weight, more preferably at least 0.1% by weight, even more preferably at least 0.25% by weight, and even more preferably at least 0.5% by weight of dispersed particles are incorporated. In the composition of the present invention, preferably no more than about 30% by weight of dispersed particles are incorporated, more preferably no more than about 15% by weight, even more preferably no more than 10% by weight.
[0191] The pH of the composition of the present invention is adjusted to preferably from about 3 to about 7, more preferably from about 3 to about 6.5, more preferably from about 3 to about 6, more preferably from about 3 to about 5.5, more preferably from about 3 to about 5, and most preferably from about 3 to about 4.5. The pH of the composition can be adjusted to as low as 3, provided that the stability and performance (e.g., foaming, mildness, and viscosity) of the formulation are not negatively affected. The pH of the composition can be adjusted to an appropriate acid value using a cosmetically acceptable organic or inorganic acid (e.g., citric acid, acetic acid, glycolic acid, lactic acid, malic acid, tartaric acid, hydrochloric acid, and combinations of two or more thereof, etc.).
[0192] Example
[0193] The following examples are intended to illustrate the present invention, not to limit the present invention.
[0194] The test methods used in the examples are as follows:
[0195] Dry precipitate mass yield test :
[0196] The following steps were used to measure the coacervate precipitation in the diluted cleaning composition. First, 2.5 g of the cleaning composition was added to a 20 mL glass scintillation vial containing 7.5 g of deionized water. The vial was capped and mixed on a VWR simulated vortex mixer for 20 seconds. Immediately after mixing, 1 mL of the bulk dilution solution was pipetted into a 1.5 mL microcentrifuge tube and pre-weighed on a Mettler Toledo XS105 analytical balance. After measuring the mass of the centrifuge tube containing 1 mL of the solution, the tube was centrifuged at 13,000 rpm in a VWR Galaxy Micro centrifuge. After centrifugation, if visible precipitates were observed, the supernatant was removed by pipette, leaving only the polyelectrolyte-rich precipitate. The centrifuge tube was then placed in a 50°C oven overnight with the lid open to remove water from the precipitate. Afterwards, the centrifuge tube containing only the dried precipitate was reweighed. Next, the mass of the centrifuge tube was subtracted from the measurement result of the centrifuge tube containing 1 mL of the diluted solution and the measurement result of the dried precipitate to calculate the mass of the total diluted solution and the dried precipitate.
[0197] The dry precipitate mass yield was calculated as the ratio of the dry precipitate material contained in the dilute solution added to the microcentrifuge tube to the total mass of cationic and anionic polyelectrolytes. In some cases, no solid / viscous precipitate was observed to appear at the bottom of the tube, but rather a single phase was observed. These samples appeared as a single phase upon dilution / centrifugation, and the dry precipitate mass yield was recorded as 0.
[0198] Viscosity Testing and Criteria for Significant Viscosity Change :
[0199] The apparent viscosity of the cleaning composition was measured on a controlled stress rheometer (AR-2000, TA Instruments Ltd., New Castle, DE, USA). Steady-state shear rate scans were performed at 25.0 ± 0.1 °C using a cone-plate geometry (50 mm diameter, 1° cone angle). Data acquisition and analysis were performed using Rheology Advantage software v5.7.0 (TA Instruments Ltd., New Castle, DE, USA). The mid-shear viscosity was taken from a shear rate of 10 s -1 The steady-state flow measurement is expressed in centipoise (cps) at a shear rate of 1s. -1 The steady-state flow measurement result is expressed in centipoise (cps) when
[0200] As used herein, the minimum significant change threshold is defined as Δη min =82.65×η 0.396, wherein η is the viscosity measured using the above scheme. This relationship between detectable viscosity differences conforms to the general prediction of power law relationships between qualitative observations, literature values and physical values and perceived amplitudes (Bergmann Tiest, WM, Vision Research, 109, 2015, 178-184, Bergmann Tiest et al., IEEE Transactions on Haptics, 6, 2013, 24-34, Stevens, JC & Guirao, M., Science, 144, 1964, 1157-1158). Then, in the case where polyelectrolyte is added to the composition (viscosity η0), we define the minimum viscosity required for asserting that there is an observable / significant change in viscosity as η min =Δη min +η0=82.65×η0 0.396 +η0.
[0201] Yield stress test :
[0202] As used herein, the term "yield stress" indicates that the viscoelastic material / sample has solid-dominated behavior. In other words, the elastic modulus must be higher than the viscous modulus in the low strain / stress plateau region of the amplitude sweep. The yield stress value is then taken as the stress at the intersection of the storage modulus G' and the loss modulus G" (G'=G"), expressed in Pascals (Pa).
[0203] The cleaning compositions of the present invention do not substantially exhibit yield stress values associated with or attributable to polyelectrolyte conditioning systems. That is, in the polyelectrolyte conditioning system, the composition contains an amount of anionic polyelectrolyte that is insufficient to provide the composition with a measurable yield stress or increase the yield stress value, as determined by the methods described herein. The increase in the measurable yield stress value is typically about 0.01 Pa or more, even more typically about 0.05 Pa or more, even more typically about 0.1 Pa or more.
[0204] The yield stress values of the cleaning compositions were measured on a controlled stress rheometer (AR-2000, TA Instruments Ltd., New Castle, DE, USA). An oscillatory strain amplitude sweep of 0.1%-1000% was performed at 25.0±0.1°C and an oscillation frequency of 1 rad / s using a cone-plate geometry (50 mm in diameter and 1° in cone angle). Data acquisition and analysis were performed using Rheology Advantage software v5.7.0 (TA Instruments Ltd., New Castle, DE, USA). The yield stress value was selected as follows: below this value, the storage modulus G' exceeds the loss modulus G", and above this value, G" exceeds G'. When G' does not exceed G" at any oscillatory stress exceeding the sensitivity of the instrument, the yield stress value is expressed as 0 Pa. Unless otherwise stated, yield stress values are given in Pascals (Pa).
[0205] Polyelectrolyte deposition test based on ellipsometry :
[0206] The polyelectrolyte deposition efficiency of the comparative example and the embodiment of the present invention during the cleaning process was evaluated on the model surface and measured using ellipsometry. First, 2.5g of the cleaning composition was added to a 20mL glass scintillation bottle containing 7.5g of deionized water and heated to 40°C. The vial was covered and stirred for 20 seconds on a VWR simulated vortex mixer. Immediately after stirring, 100μL of the diluted solution was pipetted onto a 2cm×2cm test-grade silicon wafer (University Wafer) cut chip (previously cleaned and dried with deionized (DI) water and ethanol), spread on the surface, and allowed to stand for 30 seconds. After the silicon wafer was tilted to 45°, 5mL of deionized water at 40°C was dripped onto the silicon chip and the diluted cleaning solution was rinsed from the surface. The chip was then gently wiped with a wipe and dried for 3-4 minutes.
[0207] The thickness of the deposits on the silicon wafers was measured with an α-SE spectroscopic ellipsometer (JA Woolam Co., Inc) at 5 different locations on each chip before and after treatment with the cleaning solution. The software package calculates the layer thickness by performing a standard fit on the raw ellipsometer data of the transparent film on the silicon substrate. The final average deposited layer thickness is then calculated by subtracting the average layer thickness measured before applying the diluted composition from the average layer thickness measured after applying the diluted composition.
[0208] Polydimethylsiloxane deposition test :
[0209] Evaluation of the silicone deposition efficiency of the Examples and Comparative Examples on the skin was conducted on the forearms of human volunteers and measured using attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR), similar to previous evaluations of silicones on human skin (Klimisch, HM & G. Chandra, J. Soc. Cosmet. Chem., 37, 1986, 73-87). Using REMSPEC IR TissueView TM ATR FTIR spectrometer performs ATR-FTIR measurements. -1 The interval is 900cm -1 Up to 3500cm -1 The spectra were acquired in a wavenumber range of
[0210] The polydimethylsiloxane-containing formulations of the present invention and comparative examples were prepared by incorporating a sufficient amount of pre-emulsified polydimethylsiloxane (polydimethylsiloxane droplet size of about 0.65 μm) into the formulation to obtain 5 wt% active polydimethylsiloxane in the final formulation. For example, 0.78 g of Xiameter MEM-1352 (64 wt% active polydimethylsiloxane) was added to 9.22 g of the formulation, i.e., a total of 0.5 g of polydimethylsiloxane was added to 10.0 g of the formulation.
[0211] The subject's forearm was first washed with a cleaning composition, rinsed thoroughly and dried with a sterile wipe. The cleaning composition contained sodium laureth sulfate (SLES, 5% active by weight), cocamidopropyl betaine (CAPB, 5% active by weight), sodium chloride and sodium benzoate, and the pH was adjusted to 4.5. A rectangular area of 5 cm × 7 cm was then marked on the forearm. The ATR-FTIR spectrum was then acquired at the center of the marked area. Next, 100 μL of a dimethicone-containing formulation and 100 μL of deionized water were applied to the marked area of the forearm and the area was gently rubbed with a gloved index finger for 30 seconds. After the formulation was placed on the arm for another 30 seconds, the forearm was placed 6 inches below a 37°C water flow (flow rate of 3 liters / minute) and rinsed for 10 seconds from a spray faucet (positioning the center of the spray at the center of the marked area). After rinsing, gently shake the arm, dry the area outside the marked area with a sterile wipe, and allow the marked area to air dry (5-10 minutes). After drying, obtain a 900 cm -1 Up to 3500cm -1 ATR-FTIR spectrum of
[0212] For each ATR-FTIR absorption spectrum obtained, the peak of silicon (Si) (1240-1280 cm -1) and amide II peak (1487-1780cm -1 ) minus the corresponding baseline, and the absorbance value of the siloxane peak (1240-1280cm -1 ) was calculated by using the total area under the amide II peak (1487-1780 cm -1 Then, the Si peak absorbance value after washing with the test formulation containing silicone was subtracted from the Si peak absorbance value before washing with the test formulation containing silicone. -1 The Si peak absorbance value at was used as a measure of relative dimethicone deposition since this value has been used as a measure of dimethicone concentration on the skin in previous work (Klimisch, HM & G. Chandra, J. Soc. Cosmet. Chem., 37, 1986, 73-87).
[0213] Preparation of Examples of the Invention and Comparative Examples
[0214] Different types of formulation ingredients (i.e., raw materials from various suppliers) were used to prepare the inventive examples and comparative examples. These materials and their INCI / material names, abbreviations, trade names, and suppliers are as follows:
[0215] Anionic surfactants :
[0216] Sodium lauryl ether sulfate (SLES) is sold under the trade name N70 was obtained from BASF.
[0217] C 14 -C 16 Sodium olefin sulfonate is sold under the trade name AS-40CG K was obtained from Stepan.
[0218] Sodium tridecyl sulfate is sold under the trade name TD403MFLD was obtained from Stepan.
[0219] Zwitterionic surfactants / amphoteric surfactants / nonionic surfactants :
[0220] Cocamidopropyl betaine is sold under the trade name Betain F50 was obtained from Evonik Inc., under the trade name Betain L7V was obtained from Evonik.
[0221] Coconut betaine is sold under the trade name C35 was obtained from Solvay.
[0222] Cocoamidopropyl hydroxysultaine (CAPHS) is sold under the trade name CBS was obtained from Solvay.
[0223] PEG-80 sorbitan laurate is sold under the trade name LQ (AP) was obtained from Croda.
[0224] Cationic (quaternary) conditioning polyelectrolytes :
[0225] Polyquaternium-7 (PQ-7) is sold under the trade name 7SPR was obtained from Lubrizol.
[0226] Polyquaternium-10 (PQ-10) is sold under the trade name JR-400 was obtained from Dow Chemical.
[0227] Guar hydroxypropyltrimonium chloride (cationic guar gum) is sold under the trade name C500 was obtained from Solvay Inc.
[0228] Polyquaternium-5 (PQ-5) is sold under the trade name 5 Obtained from Lubrizol.
[0229] Polyquaternium-28 (PQ-28) is sold under the trade name NT-20 was obtained from Ashland.
[0230] Polyquaternium-44 (PQ-44) is sold under the trade name UltraCare AT-1 was obtained from BASF.
[0231] Anionic polyelectrolyte :
[0232] Potassium acrylate copolymer was obtained from Lubrizol, Inc.
[0233] Acrylate copolymers are sold under the trade name Aqua SF-1 was obtained from Lubrizol.
[0234] Polyacrylate-33 is sold under the trade name 33T was obtained from Solvay.
[0235] Xanthan gum is sold under the trade name NF was obtained from Vanderbilt Minerals.
[0236] Carboxymethyl cellulose (CMC) is sold under the trade name CMC 7MF was obtained from Ashland.
[0237] Sodium (cross-linked) polyacrylate is available from Evonik Stockhausen under the trade name AP 80HS.
[0238] Wetting agent :
[0239] Glycerin was obtained from P&G Chemicals under the trade name Moon OU Glycerin.
[0240] Chelating agents :
[0241] Disodium EDTA is sold under the trade name NA was obtained from DOW.
[0242] Tetrasodium EDTA is sold under the trade name 100XL was obtained from DOW.
[0243] Organic acid / preservative :
[0244] Sodium benzoate, NF, FCC were obtained from Emerald Performance Materials.
[0245] Phenonip XB was obtained from Clariant.
[0246] Quaternary ammonium salt-15 is sold under the trade name 200 from DOW.
[0247] Beneficial Agents :
[0248] Sodium glycolate was obtained from Acros Organics.
[0249] Pre-emulsified dimethicone is sold under the trade name MEM-1352 was obtained from Dow Corning.
[0250] other :
[0251] Hexylene glycol was obtained from Penta International Crop.
[0252] The fragrance was obtained from Firmenich under the trade name Luxury 475537F.
[0253] Disodium cocoyl diacetate is sold under the trade name
[0254] CDA 40-LQ-(AP) was obtained from Croda.
[0255] From Progard TM2 Filter Millipore Direct-Q TM The system obtains deionized water (DI water, also referred to as water in the following examples).
[0256] Unless otherwise stated, all ingredients are added in such amounts as received that the composition contains the active substance in the resulting weight percentage. For example, 3.5 wt% of cocamidopropyl betaine active (as shown in Table 3a) corresponds to 9 wt% Betain F50, the latter contains 39 wt% active matter; 3.5 wt% / 39 wt%=9 wt%.
[0257] Preparation of Examples E1-E24 of the Present Invention and Comparative Examples C1-C24, C29-C34
[0258] The preparation of Examples E1-E24 of the present invention and Comparative Examples C1-C24, C29-C34 is as follows: Add the required amount of deionized water and anionic polyelectrolyte to a container of appropriate size equipped with an electric furnace and an overhead mechanical stirrer, and stir at 200-250rpm until the mixture is uniform. Then add anions and zwitterionic / amphoteric surfactants and mix until the solution becomes uniform. Then, add aqueous sodium hydroxide solution and / or citric acid to adjust to the required pH value of 6.4-6.6. After the pH value stabilizes, add cationic polyelectrolyte to the mixture. In the case where the cationic polyelectrolyte is provided as an aqueous suspension, the polyelectrolyte solution is slowly added dropwise directly to the mixture. For polyelectrolytes provided as dry powders, first prepare a premix of 9 wt% of polyelectrolyte in deionized water, and then slowly add it dropwise to the mixture. Once the mixture becomes uniform, sodium chloride and sodium benzoate are added and mixed again until uniform. Then, add aqueous sodium hydroxide solution and / or citric acid in deionized water at room temperature to adjust to the desired pH (pH 4.4-4.6 if not otherwise stated). Add deionized water qs 100 wt %, then stir the batch until homogeneous and finally pour it into a suitable storage container.
[0259] Example 1a
[0260] Examples of the present invention (E1-E3) and Precipitate Measurement of Comparative Examples (C1-C3)
[0261] Comparative Examples C1-C3 and Inventive Examples E1-E3 listed in Table 1a and the mass yield of dry precipitate (measured according to the mass yield test of dry precipitate described herein) are formulations with the same content and type of surfactant (9 wt% SLES, 2 wt% CAPB), cationic polyelectrolyte (0.6 wt% PQ-10), salt and preservative, but with different amounts of anionic polyelectrolyte added, specifically acrylate copolymers, which are well-known rheology modifiers and suspending agents. As shown in Table 1a, the mass yield of dry precipitate of Inventive Examples E1-E3 showed a measurable increase compared to Comparative Example C1 without anionic polyelectrolyte. On the other hand, Comparative Examples C2-C3 (anionic to cationic polyelectrolyte weight ratio greater than 1.2, specifically, 1.67 and 2.5, respectively) did not show an improvement in the mass yield of dry precipitate compared to C1.
[0262] Table 1a Active material weight %
[0263]
[0264]
[0265] Example 1b
[0266] Examples of the present invention (E4-E6) and Precipitate Measurement of Comparative Examples (C4-C6)
[0267] Comparative Examples C4-C6 and Inventive Examples E4-E6 listed in Table 1b and the dry precipitate mass yield (measured according to the dry precipitate mass yield test described herein) are formulations with the same components, but different levels and ratios of the components (particularly a lower concentration of cationic polyelectrolyte PQ-10 (0.2 wt %)). As shown in Table 1b, the dry precipitate mass yield of Inventive Examples E4-E6 showed a measurable increase compared to Comparative Example C4, which did not contain anionic polyelectrolyte. On the other hand, Comparative Examples C5-C6 (anionic to cationic polyelectrolyte weight ratio greater than 1.2, specifically, 1.5 and 2.5, respectively) did not show an improvement in dry precipitate mass yield compared to C4.
[0268] Table 1b Active material weight %
[0269]
[0270]
[0271] Example 2a
[0272] Analysis of Examples (E7) and Comparative Examples (C7 and C8) of the Invention Using Synthesized Cationic Polyelectrolyte (PQ-7) Output measurement
[0273] Comparative Examples C7-C8 and Inventive Example E7 listed in Table 2a and the dry precipitate mass yield (measured according to the dry precipitate mass yield test described herein) are formulations with the same amount and type of surfactant (9 wt% SLES, 2 wt% CAPB), cationic polyelectrolyte (0.6 wt% PQ-7), salt and preservative, but with different amounts of anionic polyelectrolyte added, specifically an acrylate copolymer. These compositions differ from those given in Table 1a only in the type of cationic polyelectrolyte used (synthetic PQ-7 was used instead of naturally derived cellulose-based PQ-10). As shown in Table 2a, the dry precipitate mass yield of Inventive Example E7 showed a measurable increase compared to Comparative Example C7 without anionic polyelectrolyte. The dry precipitate mass yield of Comparative Example C8 (anionic polyelectrolyte to cationic polyelectrolyte weight ratio greater than 1.2, specifically 2.5) did not show a measurable increase compared to Comparative Example C7 without anionic polyelectrolyte.
[0274] Table 2a Active material weight %
[0275]
[0276]
[0277] Example 3a-b
[0278] Examples of the present invention (E8-E9) and comparative examples with different surfactant concentrations, ratios and chemical properties (C9-C12) Precipitate Measurement
[0279] Comparative Examples C9-C12 and Inventive Examples E8-E9 and the dry precipitate mass yields (measured according to the dry precipitate mass yield test described herein) listed in Tables 3a-3b are formulations that replicate the selection of cationic polyelectrolytes, anionic polyelectrolytes, salts and preservatives in Tables 1a and 2a, but these formulations use a lower total concentration of surfactant (7 wt % total) and a different weight ratio of anionic to zwitterionic surfactants (1:1 SLES:CAPB). As shown in Tables 3a and 3b, the dry precipitate mass yields of Inventive Examples E8 and E9 (anionic to cationic polyelectrolyte weight ratio of 0.17) show a measurable increase compared to their respective corresponding Comparative Examples C9 and C11 without anionic polyelectrolytes. The dry precipitate mass yields of Comparative Examples C10 and C12 (anionic polyelectrolyte to cationic polyelectrolyte weight ratio of 2.5) do not show a measurable increase compared to their respective corresponding Comparative Examples C9 and C11 without anionic polyelectrolytes.
[0280] Table 3a Active material weight %
[0281]
[0282]
[0283] Table 3b Active material weight %
[0284]
[0285] Example 3c
[0286] The present invention examples (E10) and comparative examples (C13-C14) with different surfactant concentrations, ratios and chemical properties C14) Precipitate measurement
[0287] Comparative Examples C13-C14 and Example E10 of the present invention and the dry precipitate mass yields (measured according to the dry precipitate mass yield test described herein) listed in Table 3c are formulations that replicate the selection of cationic polyelectrolytes, anionic polyelectrolytes, salts and preservatives in Tables 1a and 2a, but these formulations use anionic surfactants of different chemical properties (C14-C16 sodium olefin sulfonates instead of SLES) and amphoteric surfactants / zwitterionic surfactants (CAPHS instead of CAPB). As shown in Table 3c, compared with its corresponding Comparative Example C13 without anionic polyelectrolytes, the dry precipitate mass yield of Example E10 of the present invention shows a measurable increase. Compared with its corresponding Comparative Example C13 without anionic polyelectrolytes, the dry precipitate mass yield of Comparative Example C14 (anionic polyelectrolyte to cationic polyelectrolyte weight ratio of 2.5) does not show a measurable increase.
[0288] Table 3c Active material weight %
[0289]
[0290] Examples 4a to 4d
[0291] Inventive Examples (E11-E14) and Comparative Examples Using Various Synthetic and Naturally Derived Cationic Polyelectrolytes Measurement of (C15-C22)
[0292] Comparative Examples C15-C22 and Inventive Examples E11-E14 listed in Tables 4a-4d and the dry precipitate mass yields (measured according to the dry precipitate mass yield test described herein) are formulations that replicate the selection of anionic polyelectrolytes, salts, and preservative levels in Table 3a, but these formulations use cationic polyelectrolytes of different chemical nature (0.6 wt% active matter), specifically, the cationic polyelectrolytes are guar hydroxypropyltrimonium chloride, PQ-5, PQ-22 and PQ-44. As shown in Tables 4a-d, the dry precipitate mass yields of Inventive Examples E11-E14 show a measurable increase compared to their respective corresponding Comparative Examples C15, C17, C19 and C21 that do not contain anionic polyelectrolytes. Comparative Examples C16, C18, C20 and C22 (anionic polyelectrolyte to cationic polyelectrolyte weight ratio greater than 1.2, specifically, 2.5) did not show a measurable increase in the mass yield of the dried precipitate compared to their respective corresponding Comparative Examples C15, C17, C19 and C21 that did not contain anionic polyelectrolytes.
[0293] Table 4a Active material weight %
[0294]
[0295] Table 4b Active material weight %
[0296]
[0297]
[0298] Table 4c
[0299] Active material weight %
[0300]
[0301] Table 4d
[0302] Active material weight %
[0303]
[0304] Example 5
[0305] The present invention examples (E15-E17) and comparative examples (C7, C11, C23, C24) precipitate measurement
[0306] Comparative Examples C7, C11, C23, and C24 and Inventive Examples E15-E17 listed in Table 5a and the dry precipitate mass yields (measured according to the dry precipitate mass yield test described herein) are formulations similar to the compositions of Tables 2a and 3b, incorporating PQ-7 and varying ratios of SLES and CAPB; however, in this case, the compositions incorporate alternative anionic polyelectrolytes, specifically potassium acrylate copolymers. Unlike AQUASF-1, potassium acrylate copolymer is a non-crosslinked polyelectrolyte with a relatively low molecular weight. As shown in Tables 5a and 5b, the mass yield of the dry precipitate of Examples E15-E17 of the present invention shows a measurable increase compared to their corresponding Comparative Examples C11 and C7 without anionic polyelectrolytes. The mass yield of the dry precipitate of Comparative Examples C23 and C24 (anionic polyelectrolyte to cationic polyelectrolyte weight ratio greater than 1.2, specifically, 2.5) does not show a measurable increase compared to their respective corresponding Comparative Examples C11 and C7 without anionic polyelectrolytes.
[0307] Table 5a Active material weight %
[0308]
[0309]
[0310] Table 5b Active material weight %
[0311]
[0312] Example 6
[0313] Preparation of Comparative Examples (C25-C28) and Measurement of Precipitates
[0314] Comparative Examples C25 and C26 described in Table 6a were prepared to replicate Examples 10 and 11 of International Patent Application WO 2005 / 023969. Where commercial materials were available, the selection of raw materials and formulation processes replicated the materials and processes cited in this publication. These compositions were prepared by the following steps:
[0315] 50% by weight of deionized water is added to a beaker. If an acrylate copolymer is included, the acrylate copolymer is added to the water while mixing. PEG-80 sorbitan laurate is then added thereto while mixing. The following ingredients are added thereto separately while mixing until a uniform mixture is obtained: cocamidopropyl betaine (Tego Betain L7V), sodium tridecyl sulfate, glycerin, polyquaternium-10, quaternium-15, and tetrasodium EDTA. The pH of the resulting solution is then adjusted with 20% by weight sodium hydroxide solution or 20% by weight citric acid solution until a final pH of about 6.3-6.6 is obtained. The remainder of the water is then added thereto.
[0316] The dry precipitate mass yield was measured according to the dry precipitate mass yield test described herein. As listed in Table 6a, the anionic polyelectrolyte to cationic polyelectrolyte weight ratio of Comparative Example C26 was 1.86, and its dry precipitate mass yield did not show a measurable increase compared to its corresponding Comparative Example C25 without anionic polyelectrolyte.
[0317] Table 6a Active material weight %
[0318]
[0319] Comparative Examples C27 and C28 described in Table 6b were prepared to simulate Examples 4 and 1 in U.S. Patent No. 7,776,318, respectively. The only modification to these formulations was the removal of glycol distearate, which is an opacifier that is insoluble in the formulation and precipitate after dilution. Such suspended solids interfere with the dry precipitate mass yield test described herein, so they are excluded from the following formulations to provide unimpeded observation of the polyelectrolyte precipitation properties of these compositions. Given the available existing commercial materials, the selection of raw materials and formulation processes repeats the materials and processes cited in this disclosure. These compositions are prepared by the following steps:
[0320] Water, preservatives, glycerin, and hexylene glycol are added to a suitably sized container equipped with a hot plate and an overhead mechanical stirrer. Once the batch is heated to 50°C, some sodium laureth sulfate is added until completely dissolved. Disodium EDTA, polyquaternium-7, and acrylates copolymer are then added in sequence, giving sufficient time between each addition to observe a completely uniform dispersion. The pH of the solution is then adjusted to 6.4-6.6 by adding dilute sodium hydroxide. The fragrance is then added to the mixture.
[0321] Subsequently, coco betaine is added, followed by disodium cocoyl diacetate. Sodium glycolate and sodium chloride are added after that. Finally, the pH of the solution is adjusted to a pH of 6.4-6.6 (for the examples containing Phenonip XB as preservative) using a diluent of sodium hydroxide and / or citric acid, and the remaining water is added in an amount to 100% by weight. The batch is mixed until homogeneous before discharging into a suitable storage vessel.
[0322] The dry precipitate mass yield was measured according to the dry precipitate mass yield test described herein. As listed in Table 6b, the composition C28 has an anionic polyelectrolyte to cationic polyelectrolyte weight ratio of 2.36, and its dry precipitate mass yield does not show a measurable increase compared to its corresponding comparative example C27 without anionic polyelectrolyte.
[0323] Table 6b Active material weight %
[0324]
[0325]
[0326] Examples 7a to 7g
[0327] The present invention examples (E18-E24) and comparative examples (C9, C11, C29-32) Precipitate Measurement
[0328] Comparative Examples C9, C11, C29-34 and Examples E18-E24 of the present invention and the dry precipitate mass yields (measured according to the dry precipitate mass yield test described herein) listed in Tables 7a-7g are formulations that replicate the selected levels of anionic polyelectrolytes, salts and preservatives in Tables 3a-3b, but these formulations use anionic polyelectrolytes of different concentrations and chemical properties. As shown in Tables 7a to 7g, the dry precipitate mass yields of Examples E18-E24 of the present invention show a measurable increase compared to their corresponding Comparative Examples C9 and C11 without anionic polyelectrolytes. The dry precipitate mass yields of Comparative Examples C29-34 (anionic polyelectrolyte to cationic polyelectrolyte weight ratio greater than 1.2, specifically, 2.5 or 3.33) do not show a measurable increase compared to their corresponding Comparative Examples C9 and C11 without anionic polyelectrolytes.
[0329] Table 7a Active material weight %
[0330]
[0331]
[0332] Table 7b Active material weight %
[0333]
[0334] Table 7c Active material weight %
[0335]
[0336]
[0337] Table 7d Active material weight %
[0338]
[0339] Table 7e Active material weight %
[0340]
[0341]
[0342] Table 7f Active material weight %
[0343]
[0344] Table 7g Active material weight %
[0345]
[0346] Examples 8a to 8e
[0347] Rheological properties of the embodiments of the present invention (E1-E3, E7-E9, E18-E20) and comparative examples (C1-C3, C7-C12, C29-31) Performance Comparison
[0348] A selection of the previously listed comparative examples and inventive examples were tested according to the Viscosity Test and Yield Stress Test described herein. The rheological properties of the compositions described in Table 1a are listed in Table 8a. The amount of acrylate copolymer included in inventive examples E1-E3, which exhibited precipitation enhancement (as shown in Table 1a), was insufficient to increase the measured viscosity above η 0.0045 wt % compared to the systems described herein without anionic polyelectrolytes. min , which is the minimum value required to indicate a significant / noticeable change in viscosity. Likewise, inventive compositions E1-E3 exhibit no measurable yield stress values. Only in comparative examples C2-C3 (which show no precipitation enhancement) is there enough acrylate copolymer (1-1.5 wt%) to cause a measurable yield stress and significant increase in viscosity. Thus, the use of crosslinked ASE acrylate copolymer as a suspending agent, thickener, or rheology modifier in inventive examples E1-E3 is outside the intended use of the polyelectrolyte.
[0349] Table 8a
[0350]
[0351] The use of acrylate copolymers similarly demonstrated no measurable yield stress or significant viscosity changes for the inventive examples, including different surfactant blends and cationic polyelectrolyte chemistries, as shown in Tables 8b-8d.
[0352] Table 8b
[0353]
[0354] Table 8c
[0355]
[0356]
[0357] Table 8d
[0358]
[0359] Table 8e shows the rheological properties of inventive examples E18 and E19, which use alternative anionic rheology-modifying polyelectrolytes (specifically, carboxymethylcellulose, polyacrylate-33, and xanthan gum). Again, these anionic polyelectrolytes are required to increase polyelectrolyte precipitation, but their use at low levels does not impart significant changes in yield stress or viscosity. Therefore, the use of these alternative anionic rheology modifiers as suspending agents, thickeners, or viscosity modifiers in the inventive examples is not within their intended use.
[0360] Table 8e
[0361]
[0362]
[0363] Example 9
[0364] Detergent polyelectrolyte film deposition on external substrates between the inventive example (E1) and the comparative examples (C1, C3) Comparison
[0365] The film / polyelectrolyte deposition efficiency of a set of comparative examples and inventive examples, all of which have comparable compositions except for the different concentrations of anionic polyelectrolytes (C1, E1, and C3 described in Table 1a), was evaluated according to the polyelectrolyte deposition test based on ellipsometer described herein. The results shown in Table 9 show that inventive example E1 shows an increase in deposited film thickness of 40% compared to comparative examples C1 and C3 (anionic / cationic polyelectrolyte active weight ratios of 0 and 2.5, respectively).
[0366] Table 9
[0367]
[0368] Example 10
[0369] Evaluation and comparison of skin feel between Example (E9) of the present invention and Comparative Example (C11)
[0370] The skin feel after washing with Comparative Example C8 and Inventive Example E6 (of comparable composition except for the different concentrations of anionic polyelectrolytes as shown in Table 3b) and then drying was qualitatively compared by three volunteers according to a sensory evaluation test. In this test, for the purpose of skin balance, the participants first washed their hands and forearms with 1 mL of a standard surfactant solution (5 wt% active sodium laureth sulfate, 5 wt% active cocamidopropyl betaine, pH 4.5, deionized water). After thorough rinsing (35-45°C tap water at about 3 liters per minute for 60 seconds), 1 mL of the test composition (C8 or E6, respectively) was dispensed into the wet palm. The participants washed their wet hands and forearms for 30 seconds by moving their hands in a circular motion on their forearms. After rinsing (35-45°C tap water at 3 liters per minute for 30 seconds), the participants dried their hands and forearms with a paper towel and allowed the hands and arms to air dry completely for about 120 seconds. The participants then described the sensory feel of the skin by running their fingers over their hands and forearms. Table 10 lists the descriptions of the dry feel of the skin after using the comparative examples and the examples of the present invention. The table shows that the addition of 0.1 wt% of the acrylate copolymer not only significantly increased the amount of precipitate measured in the relative dry precipitate mass yield test (as shown in Table 1a), but also changed the general consensus for the post-cleansed skin feel from "soft" to "powdery" after drying. This indicates that the tactile properties of the deposited film have changed.
[0371] Table 10
[0372]
[0373]
[0374] Embodiment 11
[0375] After using the formulations of the present invention (E11) and the comparative example (C15) on human skin, the effect of polydimethylsiloxane on Comparison of alkane deposition
[0376] The dimethicone deposition efficiency of the comparative example and the inventive example containing 0.6 wt % guar hydroxypropyltrimonium chloride was evaluated according to the dimethicone test described herein, and the two examples had the same composition (as described in Table 4a above) except that the concentration of anionic polyelectrolyte (C15 (no anionic polyelectrolyte) and E11 (0.1 wt % acrylate copolymer)) was different. Table 11 shows that the 1260 cm -1 The Si peak intensity at , which is related to the concentration of polydimethylsiloxane on human skin. These data show that there is a significant improvement in polydimethylsiloxane deposition from Comparative Example C15 to Inventive Example E11.
[0377] Table 11
[0378]
Claims
1. A composition comprising the following dissolved in a cosmetically acceptable aqueous medium, a) 0.1 to 1 wt. % of a cationic polyelectrolyte having a charge density of 1.5 to 3 meq / g; b) 1 to 25 wt. % of at least one surfactant, the composition comprising one or more anionic surfactants and one or more zwitterionic surfactants; and c) 0.01 to 1.2% by weight of anionic polyelectrolyte having a charge density of 0.5 to 4 meq / g, wherein the weight ratio of the anionic polyelectrolyte to the cationic polyelectrolyte is 0.05 to 1.2, wherein the composition exhibits a viscosity change below a minimum significant change threshold (Δη) when compared to substantially identical compositions min ), and exhibits no measurable yield stress or increase in yield stress value, wherein the substantially identical composition does not contain 0.01 to 1.2 weight percent of the anionic polyelectrolyte and the weight ratio of the anionic polyelectrolyte to the cationic polyelectrolyte is from 0.05 to 1.
2. 2 . The composition according to claim 1 , wherein the weight ratio of the anionic polyelectrolyte to the cationic polyelectrolyte is 0.1 to 1. 3 .
3. The composition according to claim 1, comprising 0.1 wt% to 1 wt% of the anionic polyelectrolyte.
4. The composition of claim 1, comprising 0.1 wt% to 0.8 wt% of the cationic polyelectrolyte.
5. The composition of claim 1, comprising 0.2 to 0.6 wt% of the cationic polyelectrolyte.
6. The composition according to claim 1, comprising 3 to 15 wt% of the surfactant.
7. The composition of claim 1, wherein the mass yield of dry precipitate upon dilution of the composition is greater than the mass yield of dry precipitate upon dilution of substantially the same composition.
8. The composition of claim 1, wherein the composition has a dry precipitate mass yield upon dilution that is increased by 10% or more compared to the dry precipitate mass yield of substantially the same composition upon dilution.
9. The composition of claim 1, wherein the composition has a dry precipitate mass yield upon dilution that is increased by 20% or more compared to the dry precipitate mass yield of substantially the same composition upon dilution.
10. The composition of claim 1, wherein the composition has a dry precipitate mass yield upon dilution that is increased by 40% or more compared to the dry precipitate mass yield of substantially the same composition upon dilution.
11. The composition of claim 1 , wherein the anionic polyelectrolyte is selected from polyelectrolytes derived from ethylenically unsaturated monomers comprising anionic monomers and anionizable monomers, anionic and anionizable polysaccharides and polysaccharide derivatives thereof, and anionic or anionizable polypeptides or proteins or hybrid (co)polymers.
12. A composition according to claim 1, wherein the cationic polyelectrolyte is selected from: polyelectrolytes derived from ethylenically unsaturated monomers containing cationic protonated amine or quaternary ammonium functional groups, cationic and cationizable polysaccharides and polysaccharide derivatives thereof, and cationic or cationizable polypeptides or proteins or hybrid (co)polymers.
